MIS for the Information Age Extended Learning Modules: Fifth Edition - Haag, Cummings (Mc Graw Hill, 2005)
Besar file 96 MB, Berisi file: elm, support (JPEG image, Graphics Interchange Format Image), xtras (X32 file).